On graphs with three distinct signless Laplacian eigenvalues. Issue 8 (24th May 2022) - Huang, Xueyi; Lin, Huiqiu
ABSTRACT: In this paper, all connected graphs with three distinct signless Laplacian eigenvalues of which the second one is at most five are determined.